Improving Students Writing Skills by Using Storyboard that at Junior High School - M. Reyvaldy M.P; Khusnul Khatimah (Borneo Student Research (BSR), 2022)
Purpose of study:The objectives of the study are: (1) To know using Storyboard That is effective to improve students’ narrative writing skill for the eighth-grade students’ junior high school of SMP Negeri 2 Muara Jawa in the academic year 2020/2021. (2) To find the result of students’ ability in writing when the teacher using Storyboard That for the eighth-grade students’ junior high school of SMP Negeri 2 Muara Jawa in the academic year 2020/2021. Methodology:The methodology of this research was Classroom Action Research (CAR). The research consisted of two cycles and each cycle consisted of four steps, they were: planning, acting, observing, and reflecting. The technique of collecting data was the observation, test and documentation. Results:The result of this research shows that (1) there was an improvement of writing skills using Storyboard That. It shown in cycle I the mean of post-test is higher than the mean of pre-test. The mean of post-test is (72.89) and mean of pre-test is (68.46). In cycle II the mean of post-test is higher than the mean of pre-test. The mean of post-test is (82.8) and the mean of pre-test is (72.71). (2) The result showed of T-test in cycle I is 6.871 and cycle II is 9.106. Moreover, the t-test in the cycle II is bigger than the t-test of the cycle I.There was a significant influence of using Storyboard That in improving writing skills. Applications:The subject of this research is class VIII D, which consists of 28 students at the eighth grade students’ junior high school of SMP Negeri 2 Muara Jawa